2022
DOI: 10.1007/s00018-022-04622-6
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1-expressing vocal fold epithelia modulate remodeling via effects on self-renewal and cytokeratin differentiation

Abstract: Mechanoreceptors are implicated as functional afferents within mucosa of the airways and the recent discovery of mechanosensitive channels Piezo1 and Piezo2 has proved essential for cells of various mechanically sensitive tissues. However, the role for Piezo1/2 in vocal fold (VF) mucosal epithelia, a cell that withstands excessive biomechanical insult, remains unknown. The purpose of this study was to test the hypothesis that Piezo1 is required for VF mucosal repair pathways of epithelial cell injury. Utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 114 publications
0
0
0
Order By: Relevance
“…Our results also revealed that PIEZO1 activation induces YAP accumulation in the cytoplasm, resulting in reduced YAP activity. Multiple studies have shown interactions between these pathways and their functional implications in cellular processes in other tissues/cells [41, 71-75]. Xiong et al [71] demonstrated that PIEZO1 activation promotes ovarian cancer metastasis via the Hippo/YAP signaling axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also revealed that PIEZO1 activation induces YAP accumulation in the cytoplasm, resulting in reduced YAP activity. Multiple studies have shown interactions between these pathways and their functional implications in cellular processes in other tissues/cells [41, 71-75]. Xiong et al [71] demonstrated that PIEZO1 activation promotes ovarian cancer metastasis via the Hippo/YAP signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research findings have indicated that the absence of PIEZO1 causes YAP to be excluded from the nucleus in human neural stem cells [41] and during zebrafish outflow tract valve development [73], implying that PIEZO1 may function upstream of YAP. PIEZO1 and PIEZO2 have also been identified as upstream regulators of signal transduction pathways that activate YAP for stem cell differentiation [74], also in regulating self-renewal of vocal fold mucosal epithelia [75].…”
Section: Discussionmentioning
confidence: 99%